e-Voting: VoteHere4u 2.0 / Adib Sarkawi .... [et al.] - Sarkawi, Adib; Johari, Aiza; Bujang, Azlina; Haji Bibi, Zainon (2021)
e-Voting, an Electronic Electoral Online System, or named as VoteHere4U 2.0 is developed over two years to aid voters in their voting processes, to ensure the safety of the ballot and to accelerate the process of results. It is created using web-based platform, and it can be accessed online as long as there is internet connectivity. Voters can vote multiple candidates from the same post (committee members) and contested positions, and they can view the time allocated for voting. The main issues of the existing traditional voting are time-consuming procedure (a lot of time to cast a vote and count the ballots), not cost effective (printing and ballots distributions) and involve too many personnel to assist in voting stations. Besides, it can also give results of fake voting or inaccurate data. VoteHere4U 2.0 increases the voters' participation, reduce the number of election officers, lower the costs of running elections and improve the accuracy of the results (can be calculated automatically). The system enables the organisation to conduct voting via online to cater to any organisation's needs, without the worry of changing the coding or databases. Results are produced at real time and the setup for the voting event can be prepared within short period of time. As for the commercialisation value, it is adaptable to any other event or organisation that requires voting, where the election process can be conducted in an efficient and effective manner. Based on the responses of the voters who had used this system, they claimed that the usability criteria of the system's interface were between good to excellent scales (navigation, graphic, user friendliness and consistency, content, relevance and transparency).